2020
DOI: 10.3390/agronomy10020250
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins as Targets to Improve Salt Stress Tolerance in Crops

Abstract: Salt stress drastically reduce crop productivity. In order to identify genes that could improve crop salt tolerance, we randomly expressed a cDNA library of the halotolerant sugar beet in a sodium-sensitive yeast strain. We identified six sugar beet genes coding for RNA binding proteins (RBP) able to increase the yeast Na+-tolerance. Two of these genes, named Beta vulgaris Salt Tolerant 3 (BvSATO3) and BvU2AF35b, participate in RNA splicing. The other four BvSATO genes (BvSATO1, BvSATO2, BvSATO4 and BvSATO6) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…In sugar beet, six genes coding for RBPs were identified as being able to increase salt tolerance in yeast [ 146 ]. Two of these genes participate in splicing, and the other four have only been putatively assigned as being involved in RNA metabolism.…”
Section: Manipulation Of Rbps Confers Desirable Traits In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In sugar beet, six genes coding for RBPs were identified as being able to increase salt tolerance in yeast [ 146 ]. Two of these genes participate in splicing, and the other four have only been putatively assigned as being involved in RNA metabolism.…”
Section: Manipulation Of Rbps Confers Desirable Traits In Plantsmentioning
confidence: 99%
“…Two of these genes participate in splicing, and the other four have only been putatively assigned as being involved in RNA metabolism. One of these salt-tolerance genes, BvSATO1 (which is involved in splicing), was verified in sugar beet and Arabidopsis, which showed that BvSATO1 increased salt tolerance in Arabidopsis [ 146 ].…”
Section: Manipulation Of Rbps Confers Desirable Traits In Plantsmentioning
confidence: 99%
“…Moreover, RBPs have been proposed as targets to improve stress tolerance in crops, e.g. a recent study showed that in halotolerant sugar beet (Beta vulgaris (Bv)) expression of BvSATO1, an RNA metabolism associated RBP, was repressed by salt treatment, while in Arabidopsis BvSATO1 increased salt tolerance [41].…”
Section: Drought Stress-induced Rna Interactome Changesmentioning
confidence: 99%
“…The plant cDNA library from salt-stressed sugar beet leaves used in this study was previously described in the following references [55,56]. cDNA was ligated into the λPG15 phage and inserted into the pYPGE15 shuttle expression plasmid [57].…”
Section: Screening Of a Cdna Library From Nacl-induced Sugar Beet Leaves And Isolation Of Bvhb2mentioning
confidence: 99%
“…Seeds of B. vulgaris cv Dita [55,56] were sterilized for 3 min in pure ethanol and washed three times with sterile water and placed on sterile vermiculite at 25 • C to germinate. Ten-day-old seedlings were transferred to plastic pots containing 1 L of sterilized peat moss/vermiculite (1:1, v/v).…”
Section: Plant Materials and Growth Conditions For Sugar Beetmentioning
confidence: 99%